Underground Gun Markets and the Flow of Illegal Guns into the Bronx and Brooklyn: A Mixed Methods Analysis - Braga, Anthony A.; Brunson, Rod K.; Cook, Philip J.; Turchan, Brandon; Wade, Brian (Journal of urban health, 2021)
New York City (NYC) has experienced large reductions in violent crime over the last two decades, but gun-related violence continues to pose a threat to public safety. Despite strong gun laws, high-risk individuals in NYC neighborhoods are unfortunately still able to access and misuse firearms. This research analyzes NYC’s underground gun market by closely examining the flow of guns into the two boroughs where gun violence and crime gun recoveries are most prevalent: the Bronx and Brooklyn. A mixed methods approach is utilized that consists of an assessment of firearms trace data and in-depth interviews with individuals considered to be at high risk for involvement in gun violence. Findings suggest that guns recovered in the Bronx and Brooklyn were significantly more likely to originate in states with less restrictive gun laws and more likely to have changed ownership in unregulated transactions relative to guns recovered elsewhere in NYC. Interviews revealed three primary avenues for illegal guns reaching Bronx and Brooklyn neighborhoods: high-volume gun brokers, middlemen, and individuals who make episodic low-level acquisitions from straw purchasers in other states. No subjects identified theft as a meaningful source of crime guns.